Chemical constituents of the roots of Codonopsis lanceolata - Du, Young Eun; Lee, Jin Su; Kim, Hye Mi; Ahn, Ji-Hye; Jung, In Ho; Ryu, Jong Hoon; Choi, Jung-Hye; Jang, Dae Sik (Archives of pharmacal research, 2018)
A new phenylpropanoid ( 1 ), a new alkaloid ( 11 ), and a new natural polyacetylene ( 17 ), together with nine phenolic compounds ( 2 – 10 ), five alkaloids ( 12 – 16 ), three polyacetylenes ( 18 – 20 ), three triterpenoidal saponins ( 21 – 23 ), one phenylethanoid glycoside ( 24) , and three hexyl glycosides ( 25 – 27 ) with previous known structures, were isolated from the roots of Codonopsis lanceolata . All of the isolates 1 – 27 were evaluated for their inhibitory effects on LPS-induced nitric oxide (NO) production in RAW 264.7 macrophages and cell viability in A2780 human ovarian cancer cells. Among the isolates, lancemasides A and B have a significant inhibitory effect on the production of NO in RAW264.7 cells (IC 50 values < 50 μM). In A2780 cells, lancemaside A exhibited the most potent inhibitory effect on cell viability. This is the first report on the pharmacological activities of lancemaside B ( 22 ).